2010
DOI: 10.1111/j.1753-0407.2010.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of self‐monitoring blood glucose in the management of new‐onset Type 2 diabetes mellitus: The St Carlos Study, a prospective randomized clinic‐based interventional study with parallel groups

Abstract: Background:  Intensive treatment of patients with Type 2 diabetes mellitus (T2DM) from the moment of diagnosis facilitates β‐cell recovery. Self‐monitoring of blood glucose (SMBG)‐based educational and pharmacological intervention may be better than conventional HbA1c algorithms in the treatment of newly diagnosed T2DM. Methods:  Newly diagnosed T2DM patients were randomized to either an SMBG‐based intervention or an HbA1c‐based control group (n = 99 and 62, respectively) and were followed for 1 year. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 28 publications
4
158
1
9
Order By: Relevance
“…55 The evidence for the clinical benefit of SMBG in diabetes is increasing. 9,11,[56][57][58] The current study supports the view that SMBG is cost-effective and contrasts with some previous observations. [12][13][14]59,60 These studies, however, were criticized for not having included a structured educational and therapeutic component in response to BG values.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…55 The evidence for the clinical benefit of SMBG in diabetes is increasing. 9,11,[56][57][58] The current study supports the view that SMBG is cost-effective and contrasts with some previous observations. [12][13][14]59,60 These studies, however, were criticized for not having included a structured educational and therapeutic component in response to BG values.…”
Section: Discussioncontrasting
confidence: 56%
“…[6][7][8] Studies, e.g., Structured Testing Program and Role of Self-Monitoring of Blood Glucose and Intensive Education, San Carlos, highlight the value of structured SMBG in type 2 diabetes. [9][10][11] Despite the growing evidence for the benefit of SMBG, the potential value of SMBG in type 2 diabetes is still being debated. [12][13][14] The reliability of self-monitored glucose values is a prerequisite for an efficient and safe approach to treat patients to their target.…”
Section: Introductionmentioning
confidence: 99%
“…Some participants in Australia reported using HBGM to not only monitor their diabetes, but also to understand the impact of diet and exercise on their blood glucose levels. However, in Nepal, the idea that HBGM could facilitate patient empowerment and self-management [2,29] appeared poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
“…Most studies reported hypoglycemia as total hypoglycemic events [75][76][77] (N=5) or p a r t i c i p a n t s e x p e r i e n c i n g h y p o g l y c e m i a ( N = 8). 61,62,69,73,74,78,80,82 Hypoglycemic outcomes were defined heterogeneously, with some studies based on self report 4,21,62,72,73,77,82 and others on glucose readings. 74,76,78 Twelve of the 18 studies reported measures of variability.…”
Section: Safetymentioning
confidence: 99%